Psychopathological Aspects in Childhood Hematopoietic Stem Cell Transplantation (HSCT): The Perception of Parents and Adolescents - Zanato, Silvia; Traverso, Annalisa; Tremolada, Marta; Sinatora, Francesco; Porreca, Alessio; Pozziani, Giorgio; Di Florio, Nicoletta; Capello, Fabia; Marzollo, Antonio; Tumino, Manuela; Cattelan, Chiara; Basso, Giuseppe; et al. (Frontiers in Psychology, 2017)
Abstract Background Data about psychosocial sequelae of childhood Hematopoietic Stem Cell Transplantation (HSCT) are limited and the association with a specific donor type or other medical factors is largely unknown. (Chang et al., 2012). The aim of the present study was to compare the psychological aspects of pediatric HSCT survivors with healthy peers. A secondary aim was to detect whether parents and children differed in the perception of mental health status. The influence of medical factors on psychological status was also examined. Method Thirty seven HSCT survivors (23 males) with a mean age of 14.4 years (SD=3.03; range 8.16-18.33) were recruited. Twenty-six patients underwent an allogenic HSCT (matched unrelated donor, n=20; matched sibling donor, n=6) and 11 patients received an autologous HSCT. The children psychological aspects were assessed using the Youth Self Report (YSR) (Achenbach & Rescorla, 2001) and compared to a group of matched healthy peers. At the same time, parents were requested to complete the Child Behavior Checklist 6-18 (Achenbach & Rescorla, 2001). Medical and socio-demographic data were also collected. Results HSCT survivors reported significantly higher levels of somatic complains (t27=3.14; p=0.004; mean = 3.1) when compared to healthy peers (mean=1.5). The parent CBCL scores on “child total competence” exceeded the normative clinical cutoff in 48.6% cases. Inter-rater agreement between parent and patient reports was present only in three scales: total competence score (K=0.06, p= 0.002), somatic complaints (K=0.21, p= 0.003) and attention problems (k=0.13; p=0.02). According to Ancova models, internalizing problems were more frequent in HSCT from family donors (F2=3.13; p=0.06) or in the presence of acute complications (F1=11.95; p=0.003). Conclusion In contrast to the perception of parents, pediatric HSCT survivors reported good psychological health. However, they complained about more somatic problems as compared with healthy peers. Medical aspects such as donor source and the presence of acute complications should be taken into consideration for the psychological approach in order to improve pediatric HSCT survivor care.